2019
DOI: 10.1007/s10815-019-01480-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of microfluidic sperm extraction chips as an alternative method in patients with recurrent in vitro fertilisation failure

Abstract: Purpose It is known that sperm preparation techniques in in vitro fertilisation (IVF) are intended to select the best-quality sperm. The aim of this study is to compare sperm the density gradient method and microfluidic chip (Fertile Plus) method in infertile patients by analysing fertilisation rates, pregnancy rates, and sperm morphology and DNA fragmentation rates posed by these two methods. Methods Using semen samples obtained from the patients, sperms were prepared with gradient (n = 312) and microfluidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Yildiz and Yuksel compared the fertilisation and pregnancy rates following sperm selection through density gradient centrifugation or microfluidics chip systems in couples with unexplained infertility and recurrent unsuccessful IVF treatments, some interesting results were obtained (Yildiz & Yuksel, 2019). Although no difference was observed in the fertilisation and pregnancy rates in patients with unexplained infertility, the use of a microfluidic system significantly improved the fertilisation rate in couples who received at least two IVF treatments before the study, leading the authors to conclude that this method may be beneficial for patients with recurrent unsuccessful ART treatments.…”
Section: Microfluidic Separation Of Spermatozoamentioning
confidence: 99%
“…Yildiz and Yuksel compared the fertilisation and pregnancy rates following sperm selection through density gradient centrifugation or microfluidics chip systems in couples with unexplained infertility and recurrent unsuccessful IVF treatments, some interesting results were obtained (Yildiz & Yuksel, 2019). Although no difference was observed in the fertilisation and pregnancy rates in patients with unexplained infertility, the use of a microfluidic system significantly improved the fertilisation rate in couples who received at least two IVF treatments before the study, leading the authors to conclude that this method may be beneficial for patients with recurrent unsuccessful ART treatments.…”
Section: Microfluidic Separation Of Spermatozoamentioning
confidence: 99%
“…It has been repeatedly demonstrated that the application of a microfluidic device for sperm sorting results in sperm with increased motility and significantly reduced DNA fragmentation [13,14,[23][24][25][26]. Considering these results, only a few studies have evaluated the effects of microfluidic sperm sorting on laboratory and cycle outcomes [4,15,16,18]. It is important to note that each of these studies employed the same microfluidic device as the present study [4,15,16,18].…”
Section: Discussionmentioning
confidence: 93%
“…It is important to note that each of these studies employed the same microfluidic device as the present study [4,15,16,18]. Three of these studies describe the use of the Fertile Chip and in markets outside of the United States, ZyMōt devices were known under the "Fertile" brand [4,16,18]. In April 2020, Fertile became known worldwide as the ZyMōt device.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations